Mulheres negras na música: desafios, perspectivas e enfrentamentos no Maranhão - ELIAS, Lorena de Oliveira (2024)
This study deals with the performance of five black musicians from Maranhão in artistic production and in the music market in Maranhão. The professional trajectories of Célia Maria, Célia Sampaio, Dicy Rocha, Andréa Frazão and Núbia Rodrigues make us reflect on the social working conditions of black women in the music production chain, how their victories achieved through historical struggles are made invisible and collectives based on markers of race, gender, class and generation and the challenges faced in a competitive and unequal socioeconomic context. The problem highlighted is: How do black women in music participate and support artistic production and the music market in Maranhão? Reflecting on these realities allows us to expand our reflections on the working conditions of black women and the production relations that are involved in the world of music. We brought perspectives that articulate the triangulation between varied theories and methods from the Sociology of Artistic Work to this qualitative and exploratory research, which also uses quantitative data. This work is based on bibliographic studies, documentary research, selected case studies, life stories, direct observation of specific local music scenes and semi-structured interviews in a non-probabilistic sample. A critical literature review was carried out on racial, social and gender inequality. Furthermore, a study was carried out on black female protagonism in Brazilian and Maranhão musical artistic work. From this investigation, we discovered elements that condition the artistic work of black musicians in the context of Maranhão, such as intermittent work, the absence of adequate structures for them to work, the financial and career instability of musicians, the multiple working hours, the low professional recognition and fragile incentives from the State, as we reverberate in this work, the struggles and confrontations of these women in the face of an unfair reality, where social markers of difference that translate into inequities limit their participation in the artistic work market. We bring contributions to the implementation of cultural policies with an in-depth analysis of the ways the ways in which black women act in musical work, whether as composers, arrangers, instrumentalists, singer and performers, taking into account their differences, specificities and similarities in an unequal and predominantly male local cultural artistic context.